Synergistic Effect of Composite Nickel Phosphide Nanoparticles and Carbon Fiber on the Enhancement of Salivary Enzyme-Free Glucose Sensing - Ruiz-Leon, D; Ruiz-Leon, D; Brito-Ramírez, T (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
An electrospinning method was used for the preparation of an in situ composite based on Ni2P nanoparticles and carbon fiber (FC). The material was tested for the first time against direct glucose oxidation reaction. The Ni2P nanoparticles were distributed homogeneously throughout the carbon fibers with a composition determined by thermogravimetric analysis (TGA) of 40 wt% Ni2P and 60 wt% carbon fiber without impurities in the sample. The electrochemical measurement results indicate that the GCE/FC/Ni2P in situ sensor exhibits excellent catalytic activity compared to the GCE/Ni2P and GCE/FC/Ni2P ex situ electrodes. The GCE/FC/Ni2P in situ sensor presents a sensitivity of 1050 µAmM−1cm−2 in the range of 5–208 µM and a detection limit of 0.25 µM. The sensor was applied for glucose detection in artificial saliva, with a low interference observed from normally coexisting electroactive species. In conclusion, our sensor represents a novel and analytical competitive alternative for the development of non-enzymatic glucose sensors in the future. © 2022 by the authors.
Keywords: nickel phosphide; enzyme-free glucose sensors; electrochemical sensors; salivary sensor